Promoting Longevity through Engagement in Purposeful Occupations - Jennifer K. Fortuna (Scholarworks @ WMU, 2022)
Ron Henry, an artist based in Grand Junction, CO, provided the cover art for the Fall 2022 edition of The Open Journal of Occupational Therapy (OJOT). "On the Trail to Durango" is a 36" x 36" painting made from oil and acrylic on gesso board. Ron has been creating beautiful art since he was a child. Art has provided Ron with a strong sense of purpose throughout his life. At age 90, Ron attributes his longevity to living a healthy lifestyle and regular engagement in purposeful occupations, such as painting. In this tenth anniversary issue of OJOT, Occupation and the Artist is profiling Ron to celebrate his nearly nine-decade-long career as an artist.